Metabolic Regulation, Oxygen Limitation and Heat Tolerance in a Subtidal Marine Gastropod Reveal the Complexity of Predicting Climate Change Vulnerability - Marshall, David J.; McQuaid, Christopher D. (Frontiers in Physiology, 2020)
Predictions for climate vulnerability of ectotherms have focussed on performance-enhancing physiology, even though an organism’s energetic state can also be balanced by lowering resting maintenance costs. Adaptive metabolic depression (hypometabolism) enables animals to endure food scarcity, and physically extreme and variable environmental conditions. Hypometabolism is common in terrestrial and intertidal marine gastropod species, though this physiology and tolerance of environmental change are poorly understood in subtidal benthic gastropods. We investigated oxygen limitation tolerance, hypometabolism and thermal performance in the subtidal, tropical snail Turritella bacillum. Survival, cardiac activity and oxygen debt repayment were determined when oxygen uptake was limited by gill function impairment (air exposure) or exposure to hypoxic seawater. Thermal performance and tolerance were assessed from survival and cardiac performance when heated. The ability of snails to regulate metabolism during oxygen limitation was demonstrated by their tolerance of air exposure (> 36 h) and hypoxia (> 16 h), rhymicity and reversibility of bradycardia, and inconsistent anaerobic compensation. Under acute heating, mean heart rate was temperature-insensitive in water and temperature-dependent in air. Converging or peaking of individual heart rates during heating suggest maximization of thermal performance at 38-39°C, whereas survival and heartbeat flatlining suggest an upper thermal limit exceeding 42°C. Snails survived 16 h in seawater at 38°C. Their metabolic regulation complies with the oxygen-limiting, sediment-burrowing lifestyle of the species. Although a tropical organism, the species’ thermal tolerance so far exceeds present habitat temperatures as to question its susceptibility to centenial climate warming. Our findings reveal the importance of knowing the metabolic regulatory capabilities and conserved physiological attributes of species used in climate vulnerability tests. Studies of ectotherm climate vulnerability that identify generalized trends based on physiologically similar animals may be misleading by missing information on physiological diversity.